Seven new species of spider-attacking Hymenoepimecis Viereck (Hymenoptera, Ichneumonidae, Pimplinae) from Ecuador, French Guiana, and Peru, with an identification key to the world species - Diego de Padua; Ilari Eerikki Sääksjärvi; Ricardo Ferreira Monteiro; Marcio Luiz de Oliveira (PENSOFT PUBLISHERS, 2022)
Seven new species of Hymenoepimecis Viereck are described from Peruvian Andes and Amazonia, French Guiana and Ecuador: H. andina Padua & Saaksjarvi, sp. nov., H. castilloi Padua & Saaksjarvi, sp. nov., H. dolichocarinata Padua & Saaksjarvi, sp. nov., H. ecuatoriana Padua & Saaksjarvi, sp. nov., H. longilobus Padua & Saaksjarvi, sp. nov., H. pucallpina Padua & Saaksjarvi, sp. nov., and H. rafaelmartinezi Padua & Saaksjarvi, sp. nov. In addition, the male of the Hymenoepimecis kleini Padua & Sobczak, 2015 is described, new faunistic records for the genus provided, as well as an illustrated identification key to all known species of the genus.